Manajemen Pelayanan Operasional Di Hotel Bunda Padang - Amelia Rahmi; Yuliana Yuliana (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Abstract This research is motivated by the discovery of problems related to service management in Padang Bunda Hotel. The purpose of this study is to describe service management in Padang Bunda Hotel that includes aspects of tangibility, empathy, reliability, responsiveness, assurance. This research is a descriptive study with qualitative and quantitative data. For qualitative data, informants in the study were HRD and Hotel Bunda supervisors, the informants were determined by purposive sampling. For quantitative data the population in the study was guests staying at the Padang Bunda Hotel with a total sample of 93. Non-probability sampling with incidental sampling technique. Data collection techniques for qualitative data are by observation, interviews, and documentation and for quantitative data using a research questionnaire. Data analysis for quantitative data is metabulation of data, description of data and for qualitative data that is data reduction, data presentation, drawing conclusions. The results showed planning, organizing, acting and monitoring there were some that were applied, and some that were still not implemented in service management at Hotel Padang. As in the case of employee uniform planning that has not been established because there are some constraints, and organizational structures that do not exist in some service indicators, and implementation there are some that do not go well. The results of evaluating services to guests at Bunda Hotel Padang show that one service indicator shows that the category is sufficient and 4 other indicators show a good category meaning that Hotel Bunda Padang has not provided maximum or very good service to guests.